Ответы и объяснения

  • IOriOnI
  • почетный грамотей
2012-05-23T16:23:51+04:00

5sin^4x — cos^4х = sin^2*2х

sin^4x = sin^2x*sin^2x = ((1-cos2x)/2 )^2

cos^4x=cos^2x*cos^2x = ((1+cos2x)/2 )^2

5*(((1-cos2x)/2 )^2) - ((1+cos2x)/2 )^2 = 4sin2x*cos2x

(5*(1-cos2x)^2) / 4 - ((1+cos2x)^2) / 4 = 4sin2x*cos2x

(5*(1-cos2x)^2)- ((1+cos2x)^2) / 4 = 4sin2x*cos2x

(5*(1-cos2x)^2)- ((1+cos2x)^2)=16sin2x*cos2x

4*(1-cos2x)^2 = 16sin2x*cos2x

4(1-2cos2x+cos^2 2x) = 16sin2x*cos2x

4cos^2(2x) - 8cos2x - 4 = 16sin2x*cos2x

Осталось решить данное уравнение